2020
DOI: 10.1002/pen.25354
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene Nanocomposites with Ni, Co, and Fe Carbon‐Based Magnetic Fillers

Abstract: In the present study, the effect of Ni, Co, and Fe carbonbased magnetic fillers (Ni-C, Co-C, and Fe-C) was investigated on the magnetic, mechanical, thermal, and morphological properties of polyethylene nanocomposites. The in situ polymerization technique was used to prepare nanocomposites of polyethylene from the ethylene monomer introducing small amounts of filler ranging from 1 to 2 wt.%. The metal-carbonized fillers were obtained by pyrolysis of wood sawdust activated by Ni, Co, or Fe salts. X-ray diffract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…On the one hand, the coordination bonds rupture at a high temperature and the ferric compound evenly distributes in TPU, which is equivalent to a physical filler that weakens the interaction, resulting in the decrease in thermal stability [ 41 ]. On the other hand, many researchers have widely revealed that the interaction of such Lewis acid as transition metals in the polymer can boost thermal degradation of the organic matrix, leading to adverse effects [ 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, the coordination bonds rupture at a high temperature and the ferric compound evenly distributes in TPU, which is equivalent to a physical filler that weakens the interaction, resulting in the decrease in thermal stability [ 41 ]. On the other hand, many researchers have widely revealed that the interaction of such Lewis acid as transition metals in the polymer can boost thermal degradation of the organic matrix, leading to adverse effects [ 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The existence of the metal as a block spot in the polymer and a similar morphology have been reported in other studies. [40][41][42] The micrographs do not present ller aggregation.…”
Section: Morphological Analysismentioning
confidence: 89%
“…1 It has the advantages of being cheap, light, easy to process and durable, therefore, it has become a potential substitute of traditional materials such as wood, metal and glass, for many aspects of modern human life. 2 Especially, numerous studies have been investigated to improve the mechanical, thermal, and functional properties of intrinsic polyolefin by compositing micro and nano scale fillers such as montmorillonite, [3][4][5][6] cellulose, [7][8][9][10] carbon fiber, [11][12][13][14] graphene [15][16][17] and molybdenum disulfide. 18,19 These studies have shown that micro and nano scale fillers can improve many physical and some mechanical properties of polymer, including reducing wear rate and friction significantly.…”
Section: Introductionmentioning
confidence: 99%